Analisis Beban Kerja Operator Jahit dalam Satu Line dan Pemerataan Beban Kerja dengan Metode Line Balancing: Studi Kasus: PT. PB - Faatikhah Kusuma Wardhani; Yunita Primasanti (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
This study aims to analyze the workload of sewing operators within a single production line and to equalize the workload using the line balancing method at PT. Pan Brothers. The garment industry requires high production efficiency; therefore, balanced workload distribution among operators is necessary to ensure optimal production processes. This research used an observational approach with data collection through direct observation of the sewing process, literature study, and documentation of production data. The research population consisted of 36 operators on the observed production line, analyzed through time study activities. The analyzed data included cycle time, takt time, and work processes at each workstation. The results showed that several processes had cycle times exceeding the takt time, specifically in processes number 2, 5, 6, 12, 17, 23, and 26, which caused bottlenecks and workload imbalance among operators. The calculation results indicated that the actual process time reached 520 seconds per product, while the ideal time based on takt time was 287 seconds per product, resulting in a time difference of 233 seconds or about 44% longer than the standard time. The implementation of the line balancing method was carried out by redistributing work elements from processes with high workloads to processes with remaining work capacity. The improvement results showed that the workload among operators became more balanced, the production process became more efficient, and the potential for bottlenecks could be minimized, enabling the company to achieve its production targets.